Recap of the field visits in Takeo and Kandal provinces - Vu Hong Trang (International Rice Research Institute, 2022)
The presentation discussed CGIAR Initiative on Asian-Mega Deltas team’s field visits in Takeo and Kandal provinces, Cambodia to learn agricultural systems and land use patterns in the project area, observe occurrence of climate-risks, and initially explore existing adaptation actions.